2009
DOI: 10.1001/archfacial.2008.507
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Injuries and Violence Against Women

Abstract: These results in conjunction with other presenting circumstances, such as delay in presentation, can assist the surgeon treating patients with maxillofacial injury in recognizing interpersonal violence against women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 16 publications
5
42
3
9
Order By: Relevance
“…The anatomical area with the highest rate of fracture was the nose (n=161, 39.75%); these findings are similar to the results of Arosarena et al [23] in Canada. In contrast, Motamedi [10] in Iran, Brasileiro & Passeri [1] in Brazil and Jin et al [2] in China observed a high prevalence of mandibular fractures.…”
Section: Discussionsupporting
confidence: 89%
“…The anatomical area with the highest rate of fracture was the nose (n=161, 39.75%); these findings are similar to the results of Arosarena et al [23] in Canada. In contrast, Motamedi [10] in Iran, Brasileiro & Passeri [1] in Brazil and Jin et al [2] in China observed a high prevalence of mandibular fractures.…”
Section: Discussionsupporting
confidence: 89%
“…Segundo a Organização Pan-Americana da Saú-de (Opas), a gravidade dos traumatismos pode ser classificada de acordo com os atos de violência fí-sica em lesões 17,22,23 . No entanto, Le et al 24 (2001) constataram que 14% das mulheres sofreram lesões faciais graves o suficiente para exigir a admissão no hospital, similar à pesquisa de Schraiber et al …”
Section: Severidadeunclassified
“…Vários estudos têm relatado que a faixa etária de maior prevalência de traumatismos maxilofaciais por violência contra mulheres está entre os 20 e 39 anos [2][3][4][5][7][8][9][14][15][16][17][18][19][20][21][22][23][24] . Para Santana et al 20 …”
Section: Fatores Sociodemográficos a Idadeunclassified
“…Males are four times more prone to the fracture than females with peak age between 20 to 30 years. 3 It can present in the emergency room (ER) as an isolated injury in case of violence or fight or as a part of polytrauma in case of a severe RTA. 4 RTAs are the main cause of ZMC fractures in the developing countries.…”
Section: Introductionmentioning
confidence: 99%